Anemia e inflamação intestinal nos dois primeiros anos de vida: resultados da Coorte MAL-ED, Fortaleza-Ceará, Brasil - Sousa, Lélia Sales de (2023)
Anemia is one of the most common nutritional problems in the world and can generate clinical repercussions in children. However, prospective longitudinal studies that analyze the usual intake of nutrients of complementary feeding among children with and without anemia, considering other factors such as biomarkers of intestinal inflammation during the first two years of life, are still scarce. The aim of this study was to evaluate the associations between anemia, anthropometric indicators, and nutrient intake of complementary feeding, considering the relationship between intestinal pathogen load and biomarkers of intestinal inflammation in the first two years of life. Brazilian children from the MAL-ED cohort were studied at the 7th month, 15th month, and 24th month of age. The biochemical variables analyzed were hemoglobin, ferritin, and a marker of inflammation (alpha-1-glycoprotein acid). Nutritional status was diagnosed using the z scores of the anthropometric indices weight-for-age (WAZ), length-for-age (HAZ), and weight-for-length (WHZ). Pathogen load was detected using monthly non-diarrheal stool samples. Intestinal inflammation was identified by fecal concentrations of biomarkers myeloperoxidase (MPO), neopterin (NEO), and alpha-1- antitrypsin (AAT), and the estimation of usual nutrient intake was done by monthly 24-hour dietary recall using the MSM (Multiple Source Method) statistical programs. Two logistic regression models were built to evaluate the factors associated with anemia and iron-deficiency anemia. Correlations between Hb, vitamin B12 intake, fecal biomarkers of intestinal inflammation, and pathogen load were analyzed. The prevalence of anemia decreased over the studied times, from 47.5% at month 7 to 40.2% at month 15 and 26% at month 24 (Chi-square, p=0.002). Children with anemia had lower z scores for WAZ and HAZ at month 7 (Kruskal-Walls, p < 0.05); however, at month 15, children with anemia had higher z scores for WAZ and WHZ (Kruskal-Walls, p < 0.05). Protozoa burden and total pathogen burden also decreased over the periods studied (Dunn's Post Test, p=0.000). Vitamin B12 intake was significantly lower in children with anemia at month 15 (Mann-Whitney, p=0.014). Hb was negatively correlated with MPO (Spearman, rs= -0.190, p=0.046) at month seven (7) and positively correlated with vitamin B12 intake (Spearman, rs=0.260, p=0.003) at month 15. Logistic regressions showed that male children had a higher risk for iron deficiency anemia (OR=4.57; 95% CI = 1.42 - 14.72), as well as children with higher anthropometric indicator WAZ had a higher risk for anemia (OR=1.32; 95% CI = 1.02 - 1.69). Anemia was shown to be associated with higher weight-related anthropometric indicators, with worse dietary intake of vitamin B12, and with a worse biomarker of intestinal inflammation MPO. However, anemia did not show an association with pathogen burden, although both decreased across time periods. Male gender was shown to be an important risk factor for iron deficiency anemia in the children studied. The results suggest that nutritional status, food intake, and intestinal inflammation are important factors related to anemia